Rare earth orthovanadates RVO4 (LaVO4, CeVO4) bifunctional catalyst for the synthesis of fatty acid methyl esters from Sapindus trifoliatus non-edible oil - Sadaf Khoso; Iftikhar Ahmad; Rajwali Khan; Syed Danish Ali; Mushtaq Ahmad; Amir Waseem (Applications in Energy and Combustion Science, 2025)
Investigation and enhancement of FAME synthesis from non-edible oil is one of the contemporary means to solve the inadequate amount of conventional raw materials and their high prices. This study aims to synthesize and assess the efficiency of different heterogeneous bifunctional catalysts; CeVO4 and LaVO4, to produce FAME from Sapindus trifoliatus seed oil (SPO), as a non-edible feedstock. The outcomes showed that the CeVO4 and LaVO4 catalysts revealed exceptional catalytic performance for simultaneous esterification and transesterification of SPO with a higher percentage yield. The optimum conditions were determined by varying experimental parameters such as catalyst loading, temperature, reaction duration, and the methanol-to-oil molar ratio. The CeVO4 catalyst produced the highest 98 % SPO conversion to FAME when 8 % weight of the catalyst was used with the reaction time of 100 min, temperature of 60 °C, and the methanol-to-oil ratio of 25:1. The LaVO4 catalyst produced a 94 % yield when the reaction temperature was 60 °C, the catalyst amount was 8 %, the methanol-to-oil ratio was 25:1 mol, and the reaction time was 110 min. The SPO FAME properties conform to the ASTM6751 standard specification. Besides, the stability and reusability of these heterogenous catalysts were assessed, and it was discovered that the catalysts exhibited good stability, giving the highest biodiesel conversion even after three cycles.